2010
DOI: 10.1016/j.apacoust.2010.01.007
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the acoustic and non-acoustic properties of sound absorbing materials using a three-microphone impedance tube

Abstract: This paper presents a straightforward application of an indirect method based on a threemicrophone impedance tube setup to determine the non-acoustic properties of a sound absorbing porous material. First, a three-microphone impedance tube technique is used to measure some acoustic properties of the material (i.e., sound absorption coefficient, sound transmission loss, effective density and effective bulk modulus) regarded here as an equivalent fluid. Second, an indirect characterization allows one to extract … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
90
0
6

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 138 publications
(96 citation statements)
references
References 14 publications
0
90
0
6
Order By: Relevance
“…In this situation, the experimentally measured effective density and effective bulk modulus could be used to quantify a 1 , K, K 0 , and k 0 0 from analytical inversion, 25,26 if one directly measures the porosity / and the permeability k 0 . 27 As rigid-frame behavior cannot be completely assumed here (see Fig. 5 and Appendix C), we used direct measurements of the permeability and the sound absorption of the fibrous material under study to validate this reconstruction approach.…”
Section: Resultsmentioning
confidence: 99%
“…In this situation, the experimentally measured effective density and effective bulk modulus could be used to quantify a 1 , K, K 0 , and k 0 0 from analytical inversion, 25,26 if one directly measures the porosity / and the permeability k 0 . 27 As rigid-frame behavior cannot be completely assumed here (see Fig. 5 and Appendix C), we used direct measurements of the permeability and the sound absorption of the fibrous material under study to validate this reconstruction approach.…”
Section: Resultsmentioning
confidence: 99%
“…An alternative laboratory method to measure more fundamental acoustical properties of porous media is to use the three-microphone impedance tube as suggested originally by Iwase 15 and subsequently revisited by Doutres, et al 16 Figure 2 illustrates the basic setup that can be used to measure directly the characteristic impedance and complex wavenumber. These properties can be used to estimate the dynamic density and complex compressibility from the following equations:…”
Section: Methods For Parameter Inversion Based On Asymptotic Behaviourmentioning
confidence: 99%
“…A 3-microphone impedance tube setup to measure the surface impedance of a porous layer. 16 where c 0 is the sound speed in fluid. The reproducibility of this method is discussed in ref., 12 where it was shown that the variation in the measured acoustical properties can be considerable if the material is not homogeneous.…”
Section: Methods For Parameter Inversion Based On Asymptotic Behaviourmentioning
confidence: 99%
“…24 The indirect method associated to the 3-microphone impedance tube method has been recently detailed by the authors in Ref. 25. The tube used for the measurements has a 44.5 mm inner diameter and the loudspeaker at one end generates a broadband random signal in the frequency band 200À4100 Hz.…”
Section: -3mentioning
confidence: 99%
“…The anisotropy threshold is set here to DA ¼ 1. 25 and it is found that 15 materials on 17 can be considered as isotropic ( we are interested in linking cell microstructure to nonacoustic parameters from simple models, only the 15 materials having isotropic cells are considered in the analysis. For each material, mean strut length l [lm] and thickness t [lm] are also measured.…”
Section: A Microstructurementioning
confidence: 99%